Recent insights into perceptual and motor skill learning (The computational and neural substrates of skill learning) - Lior Shmuelof (Frontiers Research Topics, 2015)
Improvements in task performance following practice can occur as a result of changes in distinct cognitive and neural processes. In some cases, we can improve our performance by selecting a more successful behavior that is already part of our available repertoire. Skill learning, on the other hand, refers to a slower process that results in improving the ability to perform a behavior, i.e., it involves the acquisition of a behavior that was not available to the controller before training. Skill learning can take place both in the sensory and in the motor domains. Sensory skill acquisition in perceptual learning tasks is measured by improvements in sensory acuity through practice-induced changes in the sensitivity of relevant neural networks. Motor skill is harder to define as the term is used whenever a motor learning behavior improves along some dimension. Nevertheless, we have recently argued that as in perceptual learning, acuity is an integral component in motor skill learning. In this special topic we set out to integrate experimental and theoretical work on perceptual and motor skill learning and to stimulate a discussion regarding the similarities and differences between these two kinds of learning.